Pembaharuan Hukum Pidana Telematika di Indonesia dalam Mengejar Kemajuan Teknologi di Era Digital 4.0/5.0 - Waldi, Wedri; Rahmat, Diding; Sudarto, Sudarto (Neolectura, 2025)
In its development, this telematics technology has used the speed and range of electromagnetic energy transmission, so that a large amount of information can be transmitted with a range, according to needs, to the entire world, even to the entire space, and is carried out in an instant. Indonesia does not have a legal definition for cybercrime. Therefore, the right to information in electronic transaction-based transactions is important in its implementation to live life in cyberspace. The research method used is normative juridical. The results of the study are The regulation of telematics criminal law in the digital era 4.0/5.0 currently in effect focuses on legal protection for the responsible use of information and communication technology, including aspects of privacy, data security, and criminal acts committed in cyberspace (cybercrime). In Indonesia, the legal basis governing telematics criminal law has been regulated in several laws and regulations, including: Law Number 19 of 2016, Law Number 27 of 2022 concerning Personal Data Protection, Law No. 1 of 2023, and other regulations are also relevant to telematics criminal law, such as: Law Number 44 of 2008 concerning Pornography and Regulation of the Minister of Communication and Information Number 5 of 2020. The renewal of telematics criminal law in Indonesia in pursuing technological progress in the digital era 4.0/5.0 is a response to the dynamic legal needs to protect society and create justice in the digital world. From the perspective of law enforcement theory, the renewal of telematics criminal law can be analyzed through three main elements: legal substance, legal structure, and legal culture.